A traceable reference for direct comparative assessment of total naphthenic acid concentrations in commercial and acid extractable organic mixtures derived from oil sands process water. Issue 3 (23rd February 2017) - Brunswick, Pamela; Hewitt, L. Mark; Frank, Richard A.; Kim, Marcus; van Aggelen, Graham; Shang, Dayue
ABSTRACT: The advantage of using naphthenic acid (NA) mixtures for the determination of total NA lies in their chemical characteristics and identification of retention times distinct from isobaric interferences. However, the differing homolog profiles and unknown chemical structures of NA mixtures do not allow them to be considered a traceable reference material. The current study provides a new tool for the comparative assessment of different NA mixtures by direct reference to a single, well-defined and traceable compound, decanoic-d19 acid. The method employed an established liquid chromatography time-of-flight mass spectrometry (LC/QToF) procedure that was applicable both to the classic O2 NA species dominating commercial mixtures and additionally to the O4 species known to be present in acid extractable organics (AEOs) derived from oil sands process water (OSPW). Four different commercial NA mixtures and one OSPW-derived AEOs mixture were comparatively assessed. Results showed significant difference among Merichem Technical, Aldrich, Acros, and Kodak commercial NA mixtures with respect to "equivalent to decanoic-d19 acid" concentration ratios to nominal. Furthermore, different lot numbers of single commercial NA mixtures were found to be inconsistent with respect to their homolog content by percent response. Differences in the observed homolog content varied significantly, particularly at the lower (n = 9–14) and higher (n = 20–23) carbon number ranges. Results highlighted the problem between using NA mixtures from different sources and different lot numbers but offered a solution to the problem from a concentration perspective. It is anticipated that this tool may be utilized in review of historical data in addition to future studies, such as the study of OSPW derived acid extractable organics (AEOs) and fractions employed during toxicological studies.